Inner alienation: diasporic consciousness in Kamila Shamsie's Salt and Saffron - Riaz, Humaira; Babaee, Ruzbeh (Australian International Academic Centre, 2015)
The purpose of this study is to investigate the ‘diasporic consciousness ‘of the fictional characters, incorporated in selected work of Pakistani expatriate writer Kamila Shamsie through the portrayal of cross-cultural differences. This study attempts to unravel the inner-alienation that sustains through specific discourses and events occurring in the lives of the expatriate fictional characters represented in Salt and Saffron (2000). The composite term used for this study is ‘diasporic consciousness’ that refers to a specific kind of awareness dominant among the contemporary transnational communities. It is also said to possess a dual nature. More specifically, it is defined in relationship to the memories of the homeland. It emphasizes on describing a myriad of experiences showing a particular state of mind and most prominently a sense of identity. Shamsie’s Salt and Saffron portrays the cross-cultural differences between Karachi and New York, and explores an irrational fear of place in which the characters initially find themselves trapped in.